Resurrection of the family Aetobatidae (Myliobatiformes) for the pelagic eagle rays, genus Aetobatus - White, William T.; Naylor, Gavin J.p. (Zootaxa, 2016)
Molecular and morphological data show that the pelagic eagle rays of the genus Aetobatus form a distinct family-level grouping separate from the true eagle rays, Aetomylaeus and Myliobatis (family Myliobatidae). The family Aetobatidae is herein resurrected to include the pelagic eagle rays and definitions are provided for this family and for the Myliobatidae. The key characters separating Aetobatidae from Myliobatidae are: pectoral fins joining head at level of eyes (vs. below level of eyes), internasal flap deeply notched (vs. nearly straight), free rear tip of pectoral fins broadly rounded (vs. angular), spiracles dorsolateral on head and visible in dorsal view (spiracles lateral on head and not visible in dorsal view), dorsal fin with obvious free rear tip (vs. no free rear tip evident, posterior margin joining dorsal surface of tail).